Peningkatan Literasi Keuangandan Investasi Generasi Z di SMK Labor Binaan FKIP UNRI Pekanbar - Lathif Arafat; Williya Meta; Alvi, Alvi; Arifin, Arifin; Tatia Patricia Belva (LPPM UMRI, 2025)
Financial knowledge regarding investments in the capital market has become increasingly important for the younger generation, particularly Generation Z, who are in the early stages of their professional lives. Investment in the capital market offers the potential for higher asset growth compared to traditional financial instruments but also comes with risks that must be managed wisely. This community service program aims to provide an overview of the importance of capital market investments for Generation Z, focusing on how they can take advantage of these opportunities early on to prepare for a better financial future. By gaining a thorough understanding of capital market instruments such as stocks, bonds, and mutual funds, Generation Z is expected to make more informed investment decisions. This community service initiative also discusses the challenges faced by Generation Z in investing and the solutions that can be implemented to overcome these obstacles. Keywords: Investment, Capital Market, Financial Literacy, Generation Z, Risk Management.